The effect of corneal crosslinking on the rigidity of the cornea estimated using a modified algorithm for the Schiøtz tonometer - Tutchenko, Larysa; Patel, Sudi; Skovron, Mykhailo; Horak, Olha; Voytsekhivskyy, Oleksiy (Indian journal of ophthalmology, 2021)
Purpose: The aim of this study was to test a method for estimating corneal rigidity before and after cross-linking (CXL) using a Schiøtz tonometer. Methods: The study was performed in the Kyiv City Clinical Ophthalmological Hospital "Eye Microsurgical Center", Ukraine. This was a prospective, consecutive, randomized, masked, case-by-case, clinical study. Corneal rigidity, indicated by the gradient (G) between lg applied weight and corresponding lg scale reading during Schiøtz tonometry, were obtained by increasing (A-mode) then reducing (D-mode) weights by two operators [A] in keratoconus, post-CXL and control subjects for estimation of (i) interoperator and (ii) intersessional errors, (iii) intergroup differences; [B] before and after CXL. Central corneal thickness CCT was measured by scanning slit pachymetry. ANOVA, t tests, linear regression were the statistical tools used. Results: Average interoperator difference (ΔG) was -0.120 (SD = ±0.294, 95%CI = -0.175 to -0.066). A significant correlation between ΔG and the mean of each pair of G values was found (r = -0.196, n = 112, P = 0.038). Intersessional differences in mean G values were insignificant (P > 0.05). There was a significant correlation between G at first session (X1) and difference between sessions (ΔG) [Operator 1, ΔG = 0.598x1-0.461, r = 0.601, n = 27, P = 0.009]. Significant intergroup differences in G were found (Operator 1, one-way ANOVA, F = 4.489, P = 0.014). The difference (Δ) between the pre-(X2) and post-CXL treatment G values was significantly associated with the pre-CXL treatment value (Operator 1, Δ = 1.970x2-1.622, r = 0.642, n = 18, P = <.001). G values were correlated with CCT in keratoconus and post-CXL. Conclusion: Corneal rigidity (G) estimated using the Schiøtz tonometer can be useful for detecting changes after CXL. However, G values are linked to CCT, can vary from time-to-time and the procedure is operator dependent.